2019
DOI: 10.1016/j.foodchem.2018.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total polyphenol content of wines by means of voltammetric techniques: Cyclic voltammetry vs differential pulse voltammetry

Abstract: Taking advantage of the low oxidation potential of polyphenolic compounds, voltammetric techniques, such as cyclic voltammetry (CV) and differential pulse voltammetry (DPV) are used rather indiscriminately. In this work, we report Total Polyphenols results (TPP) obtained by these two techniques from a set of nine samples of red and Tawny Port wine. The CV and DPV voltammograms display significant correlations with the physical-chemical parameters used to characterize red and Tawny Port wines, particularly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Eq 1 [ 27 ] was used to explore the linear relationships between the anodic current (1 st derivative) of juice samples against the following parameters that previously [ 8 , 28 ] showed correlation with electrochemical parameters, and could directly or indirectly contribute to redox reactivity of juice samples (x i ): absolute contributions of aromatic, tryptophan, and tyrosine EEM/PARAFAC fingerprints; sucrose, trans-aconitic acid, and citrate concentrations; UV/visible absorbance at 270 and 340 nm; and Brix, pH, EC, E h , TN (in gN/L). where x i is the juice property, y i is the current in mA (first derivative) at a given potential (in V), and n is 24 for juice samples representing each cultivar listed in Section II of S1 File .…”
Section: Methodsmentioning
confidence: 99%
“…Eq 1 [ 27 ] was used to explore the linear relationships between the anodic current (1 st derivative) of juice samples against the following parameters that previously [ 8 , 28 ] showed correlation with electrochemical parameters, and could directly or indirectly contribute to redox reactivity of juice samples (x i ): absolute contributions of aromatic, tryptophan, and tyrosine EEM/PARAFAC fingerprints; sucrose, trans-aconitic acid, and citrate concentrations; UV/visible absorbance at 270 and 340 nm; and Brix, pH, EC, E h , TN (in gN/L). where x i is the juice property, y i is the current in mA (first derivative) at a given potential (in V), and n is 24 for juice samples representing each cultivar listed in Section II of S1 File .…”
Section: Methodsmentioning
confidence: 99%
“…The second anodic peak appeared at 391, 383, 363, and 370 mV at the green stage, close to veraison, veraison, and maturity, respectively. This peak may result from the oxidation of malvidin anthocyanins and stilbene derivatives overlapped with the second oxidation of the catechin flavonoids [56]. The third peak close to 600 mV corresponds to the phenolic acids such as vanillic and para-coumaric acid or the second oxidation of malvidin anthocyanins [54].…”
Section: Total Phenolic Content and Total Antioxidant Capacity By Spementioning
confidence: 97%
“…More recently, Vilas-Boas et al [ 125 ] observed that the relative contribution of polyphenols with slower coupled chemical reactions to CV is performed using a scan rate typically between 50 to 100 mV/s. Their findings also revealed that CV has more sensitivity to sulfur dioxide, which creates a difficulty in the quantification of total polyphenols.…”
Section: Techniques To Quantify Astringencymentioning
confidence: 99%